Thematic analysis without paradox: sensemaking and context. Issue 1 (7th January 2022) - Ozuem, Wilson; Willis, Michelle; Howell, Kerry
Abstract : Purpose: In this paper, the authors underpin thematic analysis with a philosophical and methodological dimension and present a nuanced perspective on the application of thematic analysis in a data-driven context. Thematic analysis is a widely used qualitative analytic method; it is perceived as a transparent approach that offers single meaning. However, through Husserlian descriptive phenomenology, this paper aims to examine issues regarding subject/object and multidimensional meanings and realities. Design/methodology/approach: In most extant studies, thematic analysis has become a prescriptive approach. This emerging qualitative approach has been applied to a range of studies on social and organisational issues, knowledge management and education. However, despite its wide usage, researchers are divided as to its effectiveness. Many choose quantitative approaches as an alternative, and some disagree as to what counts as the definitive framework and process for thematic analysis. Consequently, the authors provide a level of validity for thematic analysis through emphasising a specific methodological approach based on ontological and epistemological positions. Findings: Contrary to the common mantra from contemporary qualitative researchers who claim thematic analysis is often based on a static and enduring approach, the current paper highlights the dynamic nature of a thematic analytic approach and offers a deeper understanding of the ways in which researchers can use the right approach to understand the emerging complex data context. Originality/value: Several insights regarding the literature on thematic analysis were identified, including the current conceptualisation of thematic analysis as a dynamic approach. Understanding thematic analysis through phenomenology provides a basis on which to undertake a whole range of inclusive approaches that were previously undifferentiated from a quantitative perspective.